Analisis Pemahaman Petani Kopi Dalam Membayar Zakat Hasil Pertanian (Studi Kasus Desa Tunggul Bute Kecamatan Kota Agung Kabupaten Lahat) - Via Yuki Saputri; Bunga Mar’Atush Shalihah; Zulfikri Zulfikri (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
Zakat is one of the pillars of Islam. It is obligatory for Muslims who are able to pay a portion of their wealth in accordance with Islamic law. It purifies wealth and souls, and distributes it to those entitled to it (mustahik). Tunggul Bute Village, home to extensive coffee plantations, has a significant portion of the population's income from agricultural products. However, farmers lack understanding of agricultural zakat, and they are still lacking in their practice. This study aims to determine coffee farmers' understanding of paying zakat on agricultural produce.This research uses a qualitative approach. Data sources include primary and secondary data. Primary data were obtained through observation and interviews with eleven informants, while secondary data were obtained through a literature review of scientific journals and books. Data collection techniques used in this study included observation, interviews, and documentation.The results of this study indicate that coffee farmers' understanding of zakat on coffee crops is still limited. Factors influencing their understanding include education, social environment, and habits. This limited understanding results in zakat practices not fully complying with applicable regulations. Although farmers continue to pay zakat, their practice is based more on habit than on a proper understanding of zakat regulations.